Prevention of disseminated intravascular coagulation in cancer (Hematology Meeting Reports, 2009)
Disseminated intravascular coagulation (DIC) is a syndrome that may complicate a variety of diseases, including malignant disease.1 DIC is characterized by a widespread and intravascular activation of coagulation (leading to intravascular fibrin deposition) and simultaneous consumption of coagulation factors and platelets (potentially resulting in bleeding). It is not clear to what extent the manifestation of clinically overt thrombo-embolism can be ascribed to malignancy-associated DIC. There is ample evidence for a pro-coagulant state in virtually all patients with advanced malignant disease, however, the incidence of overt DIC appears to be much lower.2 Clinically, DIC in cancer has in general a less fulminant presentation than the types of DIC complicating sepsis and trauma. A more gradual, but also more chronic, systemic activation of coagulation can proceed subclinically.3 Eventually this process may lead to exhaustion of platelets and coagulation factors and bleeding (for example at the site of the tumor) may be the first clinical symptom indicating the presence of DIC.